Malaysia's Original People Past, Present and Future of the Orang Asli /$c E dited by Kirk Endicott - Endicott, Kirk (NUS Press, 2020)
The chapters in the present volume provide a comprehensive survey of current understandings of Malaysia's Orang Asli communities, covering their origins and history, cultural similarities and differences, and the ways they are responding to the challenges posed by a rapidly changing world. The authors, a distinguished group of Malaysian (including Orang Asli) and international scholars with expertise in anthropology, archaeology, biology, education, therapy, geography and law, also show the importance of Orang Asli studies for the anthropological understanding of small-scale indigenous societies in general